Facile synthetic routes for photocatalytic Pb3(BTC)2·H2O coordination polymers. Issue 36 (22nd June 2021) - Ma, Jinxiu; Feng, Zhijuan; Wei, Jianyu; Li, Feng; Li, Taohai; Zhang, Dabin
Abstract : Pb3 (BTC)2 ·H2 O was fabricated by hydrothermal, ultrasonic and reflux methods. The results indicated that different reaction conditions have a great impact on the photocatalytic performance of the products. Abstract : Herein, we report on the successful synthesis of photocatalytic Pb3 (BTC)2 ·H2 O polymers via different methods including the surfactant-assisted hydrothermal method, ultrasonic method and reflux method. As the crystal growth is subjected to preparation atmosphere, changes in reaction conditions do not alter the crystal structures of products, but vary their morphology. High ultraviolet-light-driven photocatalytic abilities are attributed to the stable Pb3 (BTC)2 ·H2 O, and the effective productions of h + and ˙OH on the catalysts.